Assessment of the Effectiveness of Facial Expression Exercises Stimulation Using Mirror Media in Increasing Facial Muscle Strength in Hemiparetic Stroke Patients - Martono, Martono; Isnaeni, Aulia; Hartono, Hartono (Open Access Macedonian Journal of Medical Sciences, 2022)
BACKGROUND: Stroke can cause facial muscle weakness that can affect mobility, limitations in daily activities, and quality of life. One alternative solution that is non-invasive to restore facial muscle paralysis in post-stroke patients is facial expression exercises using mirror media. AIM: This study aimed to assess the effectiveness of facial muscle expression exercises stimulation using mirror media and without a mirror as media in increasing facial muscle strength in hemiparetic stroke patients. METHODS: This study used an experimental quantitative design, in which two groups of subjects who met the inclusion criteria were randomly assigned. The number of subjects who participated in this research was 60 samples divided into the intervention group (n = 30) with a mirror for facial muscle expression exercises and the control group (n = 30) without a mirror for five weeks. The research data were collected using the Fisch Facial Grading System sheet. The statistical analysis procedure of the data consisted of One-Way ANOVA, paired-samples T-test, and N-Gain score test with 95% significance. RESULTS: The difference in facial muscle strength increase was significantly greater in the intervention group (mean difference 19.4; p = 0.000). The intervention group was more effective in increasing facial muscle strength than the control group (N-Gain score 56.31%). CONCLUSION: The facial muscle expression exercise procedure using a mirror was more effective in increasing muscle strength than the group without a mirror.